2008
DOI: 10.17221/404-pse
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of total soil nitrogen and sulphur content at two conventionally managed fields

Abstract: Spatial variability of total soil nitrogen and sulphur content has been observed in two plots (I -54 ha and II -32 ha). Soil samples were taken from the topsoil in a regular grid, which was localised by GPS (individual sampling points were 80 m apart); subsequently total soil N and S contents were analysed. The average N content in plot I was 0.16%; in plot II it was 0.12%. The content of S in plots I and II was 0.09% and 0.08%, respectively. Spatial variability of total N differed in separate parts of the plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Consequently, yield dependence on soil characteristics (pH, contents of P, K, Ca, Mg, C org and N t in soil) was registered in the experiment. Vaněk et al (2008) found a largely significant positive correlation between total N content of soil and crop yield in their experimental plot. Our results show that the influence of the above-mentioned (2006) it is not possible to isolate or measure all biotic and abiotic factors that affect the yield in field but knowledge of soil fertility variability and crop yield can contribute to a rationalization of agricultural investments.…”
Section: Resultsmentioning
confidence: 91%
“…Consequently, yield dependence on soil characteristics (pH, contents of P, K, Ca, Mg, C org and N t in soil) was registered in the experiment. Vaněk et al (2008) found a largely significant positive correlation between total N content of soil and crop yield in their experimental plot. Our results show that the influence of the above-mentioned (2006) it is not possible to isolate or measure all biotic and abiotic factors that affect the yield in field but knowledge of soil fertility variability and crop yield can contribute to a rationalization of agricultural investments.…”
Section: Resultsmentioning
confidence: 91%
“…The fourth pillar of the four nutrient stewardship concept, i.e., the right place, requires more attention because it is also written down in the agronomic concept, known as site-specific nutrient management (SSNM). In general, this concept addresses differences in yields due to variability in nutrient supply to crops, both between fields or within a given field [19,20]. The main reason for the in-field differences in nutrient supply to the currently grown crop is variability in basic soil properties, consequently resulting in a spatial differentiation in water and nutrient supply to plants during the growing season [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…45 (Figure 11). In this study area, the lower contents of sulfur may be the consequence of predominantly washed-out sulfur in the form of sulfates, especially under leaching circumstances [69,78].…”
Section: Spatial Interpolation and Mapping Of Soil Propertiesmentioning
confidence: 89%